2015
DOI: 10.1590/0047-2085000000093
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for suicide in multiple sclerosis: a case-control study

Abstract: Objective To evaluated the prevalence and the suicide risk in a Brazilian sample of patients with multiple sclerosis (MS) and to identify potential factors associated with the risk of suicide. A study was performed with outpatient with MS. The risk of suicide and the presence of psychiatric disorders were assessed by version 5.0 of the Mini-International Neuropsychiatric Interview (MINI). The sample of patients at risk for suicide was matched by sex and age to a control group of patients with MS. Results Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
3
7
0
Order By: Relevance
“…Although 34% of our patients with MS had depression according to the BDI-II scale, only 33.3% were on antidepressants, indicating that this comorbidity is often not suspected or identified during the clinical assessments of these patients and that few effective therapeutic measures against depression, including both pharmacological and non-pharmacological strategies, are employed in patients with MS. Consistent with the findings of other studies 1,15,17,18 , we found that age, EDSS score, disease duration, and occupational status were important factors associated with depression in patients with MS, based on the correlation of these parameters and the higher scores in the HADS and BDI-II scales. The present study identified positive correlations, moderately between the EDSS score and presence of depression, as measured with the BDI-II, and lower between the EDSS score and presence of suicidal ideation, as measured with the BSI.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although 34% of our patients with MS had depression according to the BDI-II scale, only 33.3% were on antidepressants, indicating that this comorbidity is often not suspected or identified during the clinical assessments of these patients and that few effective therapeutic measures against depression, including both pharmacological and non-pharmacological strategies, are employed in patients with MS. Consistent with the findings of other studies 1,15,17,18 , we found that age, EDSS score, disease duration, and occupational status were important factors associated with depression in patients with MS, based on the correlation of these parameters and the higher scores in the HADS and BDI-II scales. The present study identified positive correlations, moderately between the EDSS score and presence of depression, as measured with the BDI-II, and lower between the EDSS score and presence of suicidal ideation, as measured with the BSI.…”
Section: Discussionsupporting
confidence: 92%
“…The high level of suicidal ideation we identified in our patients with MS is noteworthy. Moreover, there was a lower significant correlation between depression, as measured with the EDSS, and suicidal ideation, as measured with the BSI, in patients with MS. A study by de Cerqueira et al 1 , involving 60 patients with MS, demonstrated that 16.6% of the participants had a past history of suicide attempt or current suicide risk and noted that comorbidity with depression was significantly higher in patients with a risk of suicide than it was in a control group. Therefore, despite the intensity of the correlation, it is clear that depression can affect the quality of life, and the relationship of these parameters with the increased risk of death via suicide in individuals with MS, should alert clinicians to the issue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cerqueira et al compared two groups of MS patients: one at risk of suicide and one without it (the control group) and they found that for the control group the education level was higher. Brenner et al observed that the risk for attempting suicide was lower for both MS and non-MS patients with higher education levels, but the association for completed suicide was seen only in the non-MS group [23,41].…”
Section: Discussionmentioning
confidence: 99%